Intelligent Accident Detection With Mobile Phone Using Internet of Things - Gouthami, G; BV, Kavya; BR, Kavya; Kavita, Kavita; B, Sagar (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Things (IoT) has been growing rapidly in recent years and widely used in variety of applications such as military, marine, smart home, intelligent transportation, smart health, smart grid and smart city domains. Due to the advancement in technology and increasing traffic, road accidents and traffic hazards have increased, causing more chances of loss of life due to lack of timely help facilities. This project is an attempt towards finding solutions for timely accident notification. The proposed project records the parameters of vehicle at regular intervals of time, through a smart device installed in the vehicle and sends these values onto the Android App, vehicle owner or a third party. The system will facilitate the users in a number of ways such as notification for immediate aid in case of accident, tracking the vehicle conditions in cases of accident and disabling the vehicle remotely. The hardware components include the smart device installed in the vehicle and a mobile phone for user interaction. The smart device installed in the vehicle does not interfere with the normal functioning of the vehicle or cause overheads.